On a posteriori error estimates for space--time discontinuous Galerkin method - Dolejší, Vít; Roskovec, Filip; Vlasák, Miloslav (Proceedings of the Conference Algoritmy, 2016)
We deal with nonlinear nonstationary convection--diffusion problem. We discretize this problem by discontinuous Galerkin method in space and in time and, assuming the error is measured as a mesh dependent dual norm of residual, we present a posteriori estimate to this error measure. This a posteriori error estimate is cheap, robust with respect to degeneration to hyperbolic problem and fully computable. Moreover, we present a local asymptotic efficiency of this estimate.